Prognostic Value Of Immunoglobulin E In A Atopic Dermatitis - Chottopadhyay S P (Wolters Kluwer Medknow Publications, 2004)
Atopic dermatitis (AD) constituted about 6% of total dermatological cases and 0.14% of all new cases (165877) attending the outpatient of a hospital. Serum IgE was estimated in 115 patients with AD. It was observed that IgE level was raised in 84%, normal in 12% and below normal in 4% of cases. In the present study the family history of atopic diathesis was found in 66% of the cases. IgE level fell in 14 of 16 patients during follow up who remained free from active disease for six months or more.